Groundwater behaviour simulation of Jakarta due to excessive groundwater abstraction - Seizarwati, Wulan; Prasetya, Derry; Syahidah, Muhshonati; Rengganis, Heni (JURNAL SUMBER DAYA AIR, 2018)
Excessive groundwater abstraction is a problem that often happened in urban areas in Indonesia, including in the capital city, DKI Jakarta Province. The imbalance between rapid rate of groundwater abstraction and the very slow rate of groundwater recharge causes groundwater level depletion can not be avoided. There are cone of depression founded in some area, such as Kalideres and Sunter. In this research conducted simulation of groundwater behavior in Jakarta related to groundwater abstraction in actual condition and projection up to 2080 with some scenarios that may occur. The simulation using numerical groundwater flow model IMOD with finite difference method. Simulation result for existing condition shows cone of depression expand to the area of Pulogadung, North Bekasi, Cengkareng, and Tambora. Groundwater projection concluded that groundwater abstraction is the main factor that influence the fluctuations of groundwater table. If groundwater abstraction can be controlled (scenario 2), groundwater level can be recovered. Meanwhile, if groundwater abstraction continue increase, although there are some additional injection wells (scenario3) or recharge capacity (scenario 4), the groundwater level still decrease significantly. Even the cone of depression decline becomes deeper and wider.